Classification, Assessments and Characteristics as Factors Towards Analyzing Organizational knowledge - Zaid A., Sabeeh; S.M.F.D, Syed Mustapha; Roshayu, Mohamad (JATIT, 2017)
Knowledge is an intellectual property that is generated and circulated among members in the knowledgebased organization for the ultimate purpose of achieving sustainability and growth of businesses. Both academia and businesses have paid remarkable attention to the multifaceted field of organizational knowledge, such efforts have been, and are still being translated into enormous volume of research work and business reports. Despite the originality of some of these research efforts, there is still a lack for concise roadmaps, models and frameworks that address organizational knowledge based on adequate guidelines. This study aims to explore and synthesize previous literature that discuss the topic of organizational knowledge with the primary objective of guiding this exploration using three factors. These factors are classifications, assessments and characteristics of organizational knowledge which are considered focal points of interest for academia and industries alike. This paper followed the approach of critical analysis for research work that were published and well received by research and industrial communities. The analysis of literature considered 70 scholarly research papers that were published within the period September 2011 until September 2016 to uncover recent patterns and trends in the field of organizational knowledge. The analysis of literature guided by three main factors (classification, assessment and characteristics of organizational knowledge) indicates gaps in these previous studies. These analyses can be used for future studies that are focused more on research in the field of organizational knowledge from the perspective of these three guiding factors.